KOMPETENSI GURU PENDIDIKAN JASMANI SEKOLAH DASAR - Mulyana, Mulyana (Parameter, 2017)
This study aims to determine the competency of Physical Education Teacher in Elementary Schools (SD). The study population are all Physical Education Teachers. Samples taken from 30 teachers, while the technique is using simple random sampling. The method used is descriptive survey. Data obtained using a likert scale instrument to capture data; pedagogic competence, personal competence, sosial competence, and professional competence. The results of this study concluded that teachers of Physical Education in Primary Schools have the ability to teach well the field of Physical Education, in charge of teaching materials. But teachers are still weak in the mastery of the concept of sports science. Not all teachers can use information and communication technology in teaching Physical Education. The ability of teachers to develop themselves in a professional activity that is also not adequate. Abstrak Penelitian ini bertujuan untuk mengetahui kompetensi guru Pendidikan Jasmani Sekolah Dasar (SD). Metode penelitian yang digunakan adalah survey deskriptif. Data diperoleh dengan menggunakan instrumen skala likert untuk menjaring data; kompetensi pedagogik, kompetensi kepribadian, kompetensi sosial, dan kompetensi professional. Hasil penelitian ini menyimpulkan bahwa guru Pendidikan Jasmani di SD mampu mengajar Pendidikan Jasmani yang baik dan menguasi materi ajar. Namun disisi lain, masih terdapat kelemahan dalam penguasaan konsep keilmuan olah raga, selain itu tidak semua guru dapat memanfaatkan teknologi informasi dan komunikasi dalam pembelajaran Pendidikan Jasmani. Kemampuan guru dalam mengembangkan diri pada kegiatan profesional juga belum memadai.